P243 Elevated presepsin levels are a marker of sepsis risk in patients with inflammatory bowel diseases receiving therapy of TNF-α blockers. (27th May 2021) - Knyazev, O; Kagramanova, A; Lishchinskaya, A; Li, I; Noskova, K; Fadeeva, N; Subbotin, V; Demchenko, A; Babayan, A; Zvyaglova, M; Kulakov, D
Abstract: Background: Sepsis is a severe disease characterized by a systemic inflammatory response syndrome (SARS) associated with infection. Sepsis is registered in 1–2% of all hospitalized patients. IBD patients receiving immunosuppressive therapy have a high risk of developing sepsis. Diagnosis of sepsis is based on internationally agreed criteria. Predicting the course and outcomes of sepsis is evaluated on the MEDS (Mortality in Emergency Department Sepsis) scale. Clinical studies of a new biomarker called presepsin have shown that it is a promising early and predictive marker of sepsis Aim: to establish the role of presepsin as a marker of sepsis development in patients with inflammatory bowel diseases (IBD) receiving therapy with genetically of TNF-α blockers. Methods: The clinical status of 128 IBD patients receiving of TNF-α blockers therapy (without immunosuppressive drugs) was evaluated in the Department of IBD. 68 patients with ulcerative colitis (UC) and 60 patients with Crohn's disease (CD). Presepsin level (PSP) was determined in all IBD patients (100.0%). To stratify patients, the following criteria were used for baseline PSP levels (pg/ml): < 200 – very low risk of sepsis; - 200 - 300– low risk of sepsis; - 300 - 500– moderate risk of sepsis; - 500 - 1000 – sepsis; - ≥ 1000-severe sepsis, septic shock Results: The distribution among 128 IBD patients receiving of TNF-α blockers by presepsin level was as follows: < 200 -75 (58, 6%); - 200 – 300 – 34 (26, 6%); - 300 – 500 – 19 (14, 8%); - 500 - 1000 – 0 (0%); ≥ 1000 – 0 (0%). Of the 75 IBD patients receiving gibp and having a very low risk, none of the patients developed sepsis; of the 34 IBD patients with a low risk, one patient developed septicemia (2.9%). Among 19 patients with IBD with a moderate risk, the development of a septic condition occurred in 4 (21.0%) patients (HR-0.140, 95% CI 0.017 - 1.162; x2-2, 800; p= 0.04997). Conclusion: IBD patients receiving of TNF-α therapy, it is advisable to determine the level of presepsin in order to identify risk groups for the development of sepsis. Patients with IBD who receive of TNF-α therapy and have presepsin values in the range of 300–500 pg/ml have a significantly higher risk of developing sepsis.